Synthesis of a Lignin/Zinc Oxide Hybrid Nanoparticles System and Its Application by Nano-Priming in Maize - Daniele Del Buono; Francesca Luzi; Ciro Tolisano; Debora Puglia; Alessandro Di Michele (Nanomaterials, 2022)
Nanotechnologies are attracting attention in various scientific fields for their technological and application potential, including their use as bio-activators and nanocarriers in agriculture. This work aimed to synthesize a hybrid material (ZnO@LNP) consisting of lignin nanoparticles containing zinc oxide (4 wt %). The synthesized ZnO hybrid material showed catalytic effect toward thermal degradation, as evidenced by the TGA investigation, while both spectroscopic and contact angle measurements confirmed a modification of surface hydrophilicity for the lignin nanoparticles due to the presence of hydrophobic zinc oxide. In addition, the antioxidant activity of the ZnO@LNP and the zinc release of this material were evaluated. At the application level, this study proposes for the first time the use of such a hybrid system to prime maize seeds by exploiting the release characteristics of this material. Concerning the dosage applied, ZnO@LNP promoted inductive effects on the early stages of seed development and plant growth and biomass development of young seedlings. In particular, the ZnO@LNP stimulated, in the primed seeds, a higher content of chlorophyll, carotenoids, anthocyanins, total phenols, and a better antioxidant activity, as supported by the lower levels of lipid peroxidation found when compared to the control samples.